PEMANFAATAN BAHAN MAKANAN SEDERHANA MENJADI GIZI SEIMBANG - Sitoayu, Laras (Universitas Esa Unggul, 2018)
AbstractNutrition knowledge influence to attitude and behavior in choosing food and then can have an effect on nutrition condition of individual concerned. Nutrition knowledge has an important role in the formation of eating habits someone, because it can affect a person in choosing the type and amount of food consumed. A person who is based on good nutrition knowledge is expected to pay attention to the nutritional condition of each food consumed. Unhealthy eating habits in choosing foods can also have an impact on the nutritional status of a person. Nutritious food is not an expensive and tasty food, but it is nutritious and balanced. This activity is one of AMBARAWA FIKes - Ayo Mengabdi Bersama Mahasiswa Ilmu-ilmu Kesehatan (FIKes), with topic